2012
DOI: 10.1016/j.ijrobp.2012.07.1671
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Point to Which Single Direct Field Irradiation is Prescribed for Spinal Bone Metastases: A Survey of Practice Patterns in Japan

Abstract: Direct single fields are commonly used in radiotherapy for spinal bone metastases, and it is crucial to define the point for which the dose is prescribed. According to the guidelines from the International Bone Metastases Consensus Working Party (IBMCWP) updated in 2010, different opinions exist on whether this therapy should be prescribed to the mid-vertebral or anterior vertebral body. To our knowledge, no previous studies have surveyed practice patterns regarding this discrepancy. Therefore, we performed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Regarding the prescription point in this method, opinions in the guidelines from the International Bone Metastases Consensus Working Party were split between the mid-vertebral body and anterior vertebral body, although concerns regarding toxicity were raised for the latter (3). A survey regarding the practice patterns for this RT method concluded that a significantly higher number of respondents used dose prescription to the mid-vertebral body (17). Irrespective of these prescription points, the single PA field is inferior to AP/PA fields in terms of accomplishing homogeneous target dose distribution (18).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the prescription point in this method, opinions in the guidelines from the International Bone Metastases Consensus Working Party were split between the mid-vertebral body and anterior vertebral body, although concerns regarding toxicity were raised for the latter (3). A survey regarding the practice patterns for this RT method concluded that a significantly higher number of respondents used dose prescription to the mid-vertebral body (17). Irrespective of these prescription points, the single PA field is inferior to AP/PA fields in terms of accomplishing homogeneous target dose distribution (18).…”
Section: Discussionmentioning
confidence: 99%
“…Prescription dose was normalised to the reference point located at the geometric centre of PTVbrain. Spinal field dose normalisation point was placed in the central axis, at depth of the spinal canal 18 19 For patients with PTV lengths within 65 cm, one spinal field was used using a source-to-skin distance (SSD) of 100–110 cm.…”
Section: Planningmentioning
confidence: 99%
“…Spinal field dose normalisation point was placed in the central axis, at depth of the spinal canal. 18,19 For patients with PTV lengths within 65 cm, one spinal field was used using a source-to-skin distance (SSD) of 100-110 cm. For patients with longer spinal lengths, two direct posterior spinal fields (SSD 100 cm) were dosimetrically matched at spine depth.…”
Section: Linac-3dcrtmentioning
confidence: 99%